Transport user as an instrument of economic growth, efficiency and effectiveness - Kudláčková, Nina; Čáp, Jiří (Univerzita Pardubice, 2010)
This article focuses on the transport user. It assume, that the transport user is an instrument of economic growth, the efficiency and effectiveness. An efficient and effective transport system can significantly support the economic growth. Industry expects an effective and efficient transport system to support sustainable economic growth and enable it to compete in state, national and global markets. It expects an interconnected system of roads, rail, pipelines, ports and airports to ensure products reach markets quickly, efficiently and in good condition. Transport users are important economic agents from this point of view. Because people are creators of markets, are inputs to production and consumers of goods and services. The transport task in relation to people is therefore complex. Transport user is so very important part of the transportation planning process. This article will try to resume basic aspects and important areas influenced by the force of transport user.
Keywords: transport user; economic growth; efficiency; effectiveness